Pancreaticojejunostomy: Images of an Invagination Technique - Ben-Ishay, Offir; Assi, Zaki; Kluger, Yoram (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Sagittal view of the pancreaticojejunostomy.